The diagnosis interval influences risk factors of mortality in patients with co-existent active tuberculosis and lung cancer: a retrospective study - Mengting Xiong; Shuanshuan Xie; Yukun Wang; Chenlei Cai; Wei Sha; Haiyan Cui; Jian Ni (BMC Pulmonary Medicine, 2023)
Abstract Background Previous studies reported that tuberculosis (TB) is associated with an increased risk of lung cancer or the survival and mortality of lung cancer. However, the impact of coexisting TB on the survival of lung cancer patients was controversial. We aimed to identify risk factors on the survival rate of patients with co-existent active TB and lung cancer. Methods One hundred seventy-three patients diagnosed with active TB and lung cancer from January 2016 to August 2021 in Shanghai pulmonary hospital were selected and divided into two groups (≤ 6 months, > 6 months) according to the diagnosis interval between active TB and lung cancer (the order of diagnosis is not considered). The clinical characteristics and survival were analyzed. Univariate and multivariate logistic regression analyses were used to identify the risk factors for overall survival (OS). Results One hundred seventy-three patients were diagnosed with lung cancer and active TB. The study population exhibited a median age of 64 years, with a majority of 81.5% being male, 58.0% of patients had a history of smoking. Among those involved, 93.6% had pulmonary TB, 91.9% were diagnosed with non-small cell lung cancer (NSCLC), 76.9% were Eastern Cooperative Oncology Group (ECOG) 0–2 and 12.7% were ECOG 3–4. We observed better survival in the > 6 months group compared with the ≤ 6 months group (hazard ratio [HR] 0.456, 95% confidence interval [CI]:0.234–0.889, P = 0.017). The 1-, 3-, and 5- year OS rates were 94.2%, 80.3%, and 77.6%, respectively, in the > 6 months group and 88.3%, 63.8%, and 58.5%, respectively, in the ≤ 6 months group. Surgery (HR 0.193, [95% CI, 0.038–0.097]; P = 0.046) and ECOG Performance Status (HR 12.866, [95% CI, 2.730–60.638]; P = 0.001) were independent prognostic factors in the > 6 months group. Conclusions Patients diagnosed with lung cancer and active TB for more than half a year have a significantly better prognosis than those diagnosed within half a year. ECOG Performance Status and surgery might possibly affect the outcomes of patients with co-existent active TB and lung cancer.